Silicon interface passivation studied by modulated surface photovoltage spectroscopy - Dulanto J. (2021)
We demonstrate that the modulated surface photovoltage spectroscopy (modulated SPS) technique can be applied to investigate interface states in the bandgap, i.e. interface passivation, of crystalline silicon coated with a downshift layer such as hydrogenated aluminum nitride with embedded terbium ions by suppressing straylight with a cut-off filter. Different hydrogen contents influence the surface photovoltage spectra at photon energies below the bandgap of crystalline silicon. Modulated SPS reveals that at higher hydrogen content there is a lower signal and, thus, a lower density of surface defect states. Our experiments show that modulated SPS can become a powerful tool for characterizing defect states at interfaces which cannot be easily studied by other methods. © 2021 Published under licence by IOP Publishing Ltd.